Wage formation and monetary policy rules - Norbert Funke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
This paper characterizes the wage setting behavior in a totally unionized economy under different monetary policy rules. The wage formation strategy of the union can be either aggressive or cooperative.. As long as the union is fully cooperative and in the absence of shocks, the government can completely reach its macroeconomic targets: full employment and price stability. If, however, the union becomes aggressive, a constant money supply rule has a nominal wage inflation bias under certain plausible- assumptions. By changing the rules of the game, e.g. following a nominal GNP or price level (inflation) rule, wage demands would be lower and the economy better off.
Keywords: 330; Lohn; Geldpolitik; Theorie